2023
DOI: 10.1107/s2414314622012093
|View full text |Cite
|
Sign up to set email alerts
|

(S)-2-[(S)-2,2,2-Trifluoro-1-hydroxyethyl]-1-tetralone

Abstract: The crystal structure of the title compound, C12H11F3O2, was elucidated by low-temperature single-crystal X-ray diffraction. The enantiopure compound crystallizes in the Sohncke space group P21 and features one molecule in the asymmetric unit. The structure displays intermolecular O—H...O hydrogen bonding, which links the molecules into infinite chains propagating parallel to [010]. The absolute configuration was established from anomalous dispersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…When Ru II -catalyzed DKR-ATH was applied to CF 3 CO-substituted benzofused cyclic ketones, it was observed that single or double reduction occurs, yielding either diastereo-and enantiopure monoalcohols or 1,3-diols (Cotman et al, 2016). The crystal structure of the mono-reduced product (S)-2-[(S)-2,2,2-trifluoro-1-hydroxyethyl]-1-tetralone has been described previously (Motaln et al, 2023) and herein the crystal structure of the corresponding diol is presented.…”
Section: Structure Descriptionmentioning
confidence: 96%
“…When Ru II -catalyzed DKR-ATH was applied to CF 3 CO-substituted benzofused cyclic ketones, it was observed that single or double reduction occurs, yielding either diastereo-and enantiopure monoalcohols or 1,3-diols (Cotman et al, 2016). The crystal structure of the mono-reduced product (S)-2-[(S)-2,2,2-trifluoro-1-hydroxyethyl]-1-tetralone has been described previously (Motaln et al, 2023) and herein the crystal structure of the corresponding diol is presented.…”
Section: Structure Descriptionmentioning
confidence: 96%